Analysis of The Meaning of Dayok Nabinatur Food as Local Wisdom In Batak Simalungun Cultural Wedding Events (Semiotic Study) - Veni Melinda Sinaga; Jumaria Sirait; Vita Riahni Saragih; Marlina Agkris Tambunan; Immanuel Doclas Belmondo Silitonga (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
This study analyzes the meaning of Dayok Nabinatur as local wisdom in Batak Simalungun wedding ceremonies through a semiotic approach. Dayok Nabinatur, a traditional dish, is studied not only as a culinary element but also as a bearer of cultural and philosophical signs. Using Charles Sanders Peirce’s semiotic theory, this study explores the symbolic meaning contained in each ingredient and the preparation process of Dayok Nabinatur. Data was collected through ethnographic observation and in-depth interviews with community leaders and culinary experts. The results of the study reveal that Dayok Nabinatur functions as a signifier of harmony, prosperity, and family ties in the Batak Simalungun community. The components of the dish and its preparation methods are interpreted as icons, indices, and symbols that reinforce cultural values and social relationships. This study contributes to a deeper understanding of how traditional foods embody and communicate cultural meanings in the context of Batak Simalungun weddings..